Collisions of Legal Consciousness in the Minds of Russian Students: A Critical Breach between the Moral and the Legal - L Yu Bronzino; V E Grebneva (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2013)
The legal consciousness of a contemporary Russian is characterized by contradictions, which, as the article argues, are of a fundamental-critical nature, being a manifestation of the crisis in contemporary (not only Russian) society, connected with the formation of the indefinite society. The article presents the results of the methodological experiment which confirmed the thesis of a breach between the moral and legal aspects in the legal consciousness of Russian students.